Children with bronchiectasis have poorer lung function than those with cystic fibrosis and do not receive the same standard of care. Issue 12 (1st September 2019) - Prentice, Bernadette J.; Wales, Sandy; Doumit, Michael; Owens, Louisa; Widger, John
Abstract: Background: Children with cystic fibrosis (CF) are routinely managed in a multidisciplinary clinic at tertiary pediatric centers. However, children with bronchiectasis may not be managed in the same way. We sought to compare the management model and clinical outcomes of children with bronchiectasis with children diagnosed with CF, in a single pediatric center. Methods: We identified patients with bronchiectasis from hospital medical records at an urban tertiary pediatric hospital and identified a sex‐ and age‐matched CF patient at the same center to compare lung function, nutritional status, frequency of physiotherapy and respiratory physician visits, and number of microbiological samples taken for bacterial culture. Results: Twenty‐two children with bronchiectasis were identified, mean (standard deviation [SD]) age was 11 (3) years. The most common known etiology for bronchiectasis was postinfective (6 of 22) but was unknown in 8 of 22. The cohort with bronchiectasis had poorer lung function (FEV1 mean [SD] percent predicted 78.6 [20.5] vs 94.5 [14.7], P  = .005) and had less outpatient reviews by the respiratory physician ( P  < .001) and respiratory physiotherapist ( P  < .001) when compared to those with CF. Nutritional parameters did not differ between the groups. Many children (10 of 22, 45%) with bronchiectasis did not have any microbiological respiratory tract samples taken for evaluation. Conclusion: Children with bronchiectasis at this institution have poorer lung function than children with CF, and are deserving of improved multidisciplinary care.